2014
DOI: 10.1146/annurev-nutr-071812-161215
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mediators Governing Iron-Copper Interactions

Abstract: Given their similar physiochemical properties, it is a logical postulate that iron and copper metabolism are intertwined. Indeed, iron-copper interactions were first documented over a century ago, but the homeostatic effects of one on the other has not been elucidated at a molecular level to date. Recent experimental work has, however, begun to provide mechanistic insight into how copper influences iron metabolism. During iron deficiency, elevated copper levels are observed in the intestinal mucosa, liver, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 122 publications
(165 reference statements)
3
69
0
1
Order By: Relevance
“…Given these facts, it was logical to postulate that copper influences intestinal iron transport. This would, in fact, not be surprising, given the well-established iron-copper interactions in mammals that have been noted previously 1214 . Exactly how, and if, dietary copper affects intestinal iron absorption has, however, not been definitively established.…”
Section: Introductionmentioning
confidence: 66%
“…Given these facts, it was logical to postulate that copper influences intestinal iron transport. This would, in fact, not be surprising, given the well-established iron-copper interactions in mammals that have been noted previously 1214 . Exactly how, and if, dietary copper affects intestinal iron absorption has, however, not been definitively established.…”
Section: Introductionmentioning
confidence: 66%
“…Micronutrient profiling revealed a robust decrease in iron content of breast milk in mice with an intestinal disruption of HIF-2α. Although iron levels have been shown to be important in regulation of other micronutrients, no significant change was observed in any other metals assessed (45). DMT-1, FPN, and TFR-1 are expressed in the mammary gland and transport iron to milk.…”
Section: Discussionmentioning
confidence: 83%
“…Most hepatic copper is incorporated into the CP protein, which is subsequently secreted from hepatocytes into the blood [20]. One study compared different acute phase proteins and showed that CP is significantly increased compared to other proteins in exudative pleural effusion [21].…”
Section: Discussionmentioning
confidence: 99%